Perkembangan Pendidikan IPS di Indonesia pada Tingkat Sekolah Dasar - Nabilla Nur Fauziah; Randita Lestari; Tin Rustini; Muh. Husen Arifin (AR-RIAYAH : Jurnal Pendidikan Dasar, 2022)
Social Sciences Education is a study of the social sciences and humanities that aims to improve citizens' abilities. The social studies disciplines in Indonesia are aimed at helping students gain information, awareness, and analytical skills regarding a society's social conditions as they prepare to enter a dynamic society. The foundation of social studies is reality and social phenomena, which are achieved through an interdisciplinary approach from many social science areas. Over time, social studies education in elementary schools has undergone various developments and curriculum changes. In Indonesia, social science education was introduced in 1975 and used the 1975–2006 curriculum. With the materials separately, the development and renewal of the curriculum took place so as to create the 2013 curriculum, which packs social studies education materials in an integrated manner. These changes and developments aim to improve the quality of Indonesian education and create students who can think critically in order to meet the challenges of the times so that they can compete globally. The author collects data through a literature review in order to write this scientific essay. It is intended that by writing this article, the author will be able to describe the evolution of social studies education in Indonesia at the primary school level, as well as the advantages of the many curricula utilized.